2017
DOI: 10.1515/cclm-2016-0536
|View full text |Cite
|
Sign up to set email alerts
|

Looking beyond linear regression and Bland-Altman plots: a comparison of the clinical performance of 25-hydroxyvitamin D tests

Abstract: The presented approach allows the prediction of the clinical consequences of a 25OHD method transfer. Differences in the clinical classification of assay results are likely encountered when transferring to a new method, even between assays standardized according to the Vitamin D Standardization Program (VDSP) Reference Method Procedure (RMP).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Dowling et al had reported over-estimation of 25(OH)D measurements in the Roche assay due to the cross-reactivity of 24,25(OH) 2 D present in the samples [8]. Karvaly et al had demonstrated the extent of the discrepancies between seven different methods on the interpretation of vitamin D status and found the DiaSorin Liaison had identified significantly more hypovitaminosis cases, whereas fewer cases were detected by IDS-iSYS D assay [9]. Disparity can also occur in specific population groups; Hara et al had reported falsely high 25(OH) D in serum samples from in infants and postpartum women produced by the Diasorin radioimmunoassay (RIA).…”
Section: Immunoassays For 25(oh)dmentioning
confidence: 99%
“…Dowling et al had reported over-estimation of 25(OH)D measurements in the Roche assay due to the cross-reactivity of 24,25(OH) 2 D present in the samples [8]. Karvaly et al had demonstrated the extent of the discrepancies between seven different methods on the interpretation of vitamin D status and found the DiaSorin Liaison had identified significantly more hypovitaminosis cases, whereas fewer cases were detected by IDS-iSYS D assay [9]. Disparity can also occur in specific population groups; Hara et al had reported falsely high 25(OH) D in serum samples from in infants and postpartum women produced by the Diasorin radioimmunoassay (RIA).…”
Section: Immunoassays For 25(oh)dmentioning
confidence: 99%